In vivo nephroprotective effect of herbal plants towards gentamicin-induced nephrotoxicity: A literature review - Erlyn Dwi Cahyani; Rahmad Aji Prasetya; Izzatul Ma'rifah; Deby Nanda Tri Widia; Tiara Sri Dewi; Sulfa Putri (Jurnal Ilmiah Farmasi, 2022)
Background: Gentamicin can cause nephrotoxicity due to accumulation in proximal tubules then triggering free radicals generation that damage the nephrons. In response, our body produces endogenous antioxidants. However, extensive formation of free radicals requires exogenous antioxidants which can be obtained from herbal plants to compensate. Thus, rigorous preclinical and clinical studies are needed to prove the efficacy of medicinal plants that protect the kidneys from gentamicin nephrotoxicity. Objective: This review article provides a scientific overview of the herbal plants’ nephroprotective activity towards gentamicin induction in vivo. Method: A literature search through ScienceDirect database in July 2022 using the keywords “kidney damage”, “herbal plants”, and “gentamicin” resulted in 12 articles to be reviewed. Results: We found 12 herbal plants proven to reverse the declining kidney function. We observed significant attenuation in elevated Blood Urea Nitrogen (BUN) and/or creatinine levels in subject animals receiving herbal plants compared to the gentamicin-induced group. This nephroprotective effect is due to the content of several compounds such as flavonoids, polyphenols, and tannins. Although each plant contains different compounds, all of them have antioxidant activity that inhibits oxidation in nephrons due to gentamicin induction. Conclusion: The antioxidant compounds contained in herbal plants have the potential to prevent or treat nephrotoxicity due to gentamicin usage.